Aesthetic surgical management of Peripheral Ossifying Fibroma – A case report - T.S., Nilima; Sadasivan, Arun; Koshi, Elizabeth; Vallabhan, Chitra Girija; Vijayakumar, Steffi (South Eastern European Journal of Public Health, 2024)
AIMS AND BACKGROUND: Peripheral ossifying fibroma (POF) is a non-neoplastic gingival enlargement of connective tissue origin observed most frequently in females at second and third decade of life. POF can be a reason for diagnostic dilemma owing to its atypical clinical presentation as well as its predilection for recurrence which might result from inadequate management. CASE DESCRIPTION: An 18 years old female patient presented with a case of recurrent, asymptomatic gingival overgrowth in the left mandibular premolar area. Clinically, the lesion appeared as a firm, pale pink, sessile, exophytic growth with an erythematous border that measured about 1 centimetre. which was asymptomatic. After surgical excision and thorough debridement, absorbable fibrillar collagen matrix was used to treat the soft tissue defect in the biopsy site. Given the high recurrence rate linked to these lesions, the patient was enrolled in a strict post-operative follow-up regimen after histopathologic assessment confirmed the diagnosis of peripheral ossifying fibroma. At the three-month post-operative appointment, the soft tissue defect from the excisional biopsy was seen to be healing excellently, and subsequent follow-up visits revealed no signs of recurrence of the lesion. CONCLUSION: In this case report, we demonstrate the viability of using fibrillar collagen matrix as a biological dressing to treat intraoral soft tissue defects that arise from intraoral lesions that are surgically removed. Surgical excision of peripheral ossifying fibroma can be challenging to manage because it leaves a large soft tissue defect that can lead to recession in the resected region. Excision of such a lesion may also result in excessive bleeding and a delayed healing process with exposure of bone. Prompt application of collagen fibres following excision aids in avoiding the aforementioned post-surgical complications.